Anti-Phospholipase A2 Receptor Antibodies as Diagnostic Modality in Primary Idiopathic Membranous Nephropathy: Experience of Two Tertiary Care Centers - Rath, Ashutosh; Badwal, Sonia; Tewari, Rohit; Sengupta, Prashant; Kumar, Arun (Annals of Pathology and Laboratory Medicine, 2018)
Background Phospholipase A2 receptor (PLA2R), an IgG4 subclass antibody, is being extensively studied for diagnosis, monitoring and prognostication of cases of primary membranous nephropathy (MN). There is significant heterogeneity within the studies with most of the work targeted towards circulating PLA2R antibody. The present study evaluates PLA2R glomerular staining in primary MN as a diagnostic test in conjunction with the serology. Methods: Diagnostic study. We studied paraffin-embedded kidney biopsies of 60 patients with biopsy-proven MN, for the presence of PLA2R in glomerular immune deposits utilising immunohistochemistry. 60 cases of non MN cases along with autopsy renal tissue were used as controls. A subset of patients (n=40) were tested for circulating PLA2R antibody using quantitative sandwich enzyme immunoassay. Results: Positive PLA2R expression was present in 37/39 (94.8%) cases of primary MN, 5/21 (23.8% ) of secondary MN and 4/60 (6.6%) of non MN group. The expression was detected along glomerular basement membrane in granular pattern of varying intensities. Circulating anti-PLA2R antibodies were detected in 71.42% of primary MN cases, 8.3% of secondary MN cases and non MN group. PLA2R immunostaining exhibited higher sensitivity and modest specificity for differentiating primary from secondary MN (ROC-AUC :0.885 of IHC vs ROC-AUC: 0.776 of serology). The immunostaining however required precision and expertise to read the results. Conclusion: Tissue staining of PLA2R antibody in renal biopsies will be complementary to serology and two done in conjunction will be better discriminator between primary and secondary MN.